Predictors of Halal Product Awareness and Its Relationship with Purchasing Intention: Evidence from Turkey - Metin Saygılı; Nihal Sütütemiz (Türkiye İslam İktisadı Dergisi)
The main purpose of this study is to analyze the relationship of halal product awareness and purchasing intention by using the health consciousness, subjective norms and halal certificate information of Muslim consumers as predictors. In this study where the Theory of Planned Behavior was taken as a basis, a quantitative research design was followed. In this context, the popula- tion of the study included Muslim consumers in Turkey at and over the age of 18 who have purchasing capacity. The drop-collect and online questionnaire technique was utilized in the study to collect the data. The data of a total of 2289 participants were included in the analysis. In testing the research model, the Structural Equation Modeling method which is a multivariate and sophisticated type of analysis was employed. The results showed that halal product awareness had a positive effect on the purchasing intentions of the participants for halal products. Additionally, it was determined that the three variables taken as the predictors of halal product awareness had statistically significant effects on halal product awareness. The variable with the highest effect among these variables was halal cer- tificate information.